INFLEKSI VERBA DALAM ALBUM OVEREXPOSED MAROON 5: KAJIAN MORFOSINTAKSIS (INFLECTION OF VERBS IN MAROON 5’S OVEREXPOSED ALBUM: A MORPHOSYNTAX STUDY) - Ilham Munandar; Wagiati Wagiati (Balai Bahasa Jawa Barat, 2021)
AbstractAs one of a class of lexical units, verbs can be identified by morphosyntax, which is the relation between morphology and syntax. Inflection is often used by writers or linguists to get a more specific meaning tailored to the circumstances of a sentence. Inflection of verbs or conjugation are influenced by several factors that cause the verb form and meaning to change. This writing discusses the inflection of verbs in Maroon 5’s Overexposed album song lyrics as a morphosyntax study. using qualitative descriptive method. The theory about inflections by O’Grady &Archibald and Herring are used as references to analyze the data. The result showsthat there are three types of inflection of verbs in Overexposed album, namely (1) suffix –s, functions as the third-person singular pronoun, (2) suffix –ing, functions as the progressive form, and (3) suffix –ed, functions as the past tense.AbstrakSebagai salah satu kategori unit leksikal, verba dapat diidentifikasi secara morfosintaksis, yaitu persinggungan antara kajian morfologi dan sintaksis. Infleksi sering digunakan oleh para penulis atau ahli bahasa untuk mendapatkan makna yang lebih spesifik yang disesuaikan dengan keadaan dalam suatu kalimat. Infleksi verba atau konjugasi terjadi karena dipengaruhi oleh beberapa faktor yang menyebabkan suatu verba berubah bentuk dan juga maknanya. Penelitian ini membahas infleksiverba dalam kajian morfosintaksis yang menjelaskan bentuk infleksi verba yang terdapat pada lirik lagu Maroon 5 dalam album Overexposed. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Teori mengenai infleksi oleh O’Grady & Archibald serta Herring digunakan sebagai acuan untuk menganalisis data. Hasil penelitian menunjukkan bahwa ada tiga jenis infleksi verba yang terdapat dalam album Overexposed di antaranya (1) sufiks –s yang berfungsi sebagai penanda pronomina persona ketiga tunggal, (2) sufiks –ing yang berfungsi sebagai penanda progressive, dan (3) sufiks –ed yang menunjukkan bentuk past tense.